Greek economic crisis and its impact on regional development and policy - Yiannis Saratsis; Angelos Kotios; George Galanos (European Regional Science Association (ERSA), 2012)
Greek economic crisis and its impact on regional development and policy In the past 3 decades the main financial support mechanism for the development of Greek Regions was the European Cohesion Policy and less national instruments as the Regional Investment Framework and public investments. Under the provisions of Cohesion Policy, a significant amount of money was given to all countries, including Greece of course, in order to accelerate the development dynamics in Europe. Moreover, this money was spent in specific interventions that were estimated to have positive influence in regional competitiveness and promote regional development. The current economic crisis that has emerged in the Greek economy has already an enormous effect on several national and regional development indicators like GDP growth, unemployment, social exclusion, industrial production, bank credits etc., and also has shrunk the available financial resources for public and private investment through the Community Structural Funds and the national regional policy funds. This is a negative perspective regarding the Greek Regions that still face many structural problems, that have been deteriorated during the current crisis. This article discusses some of the above problems, and focuses on the changes that need to be implemented in Greek Regional Policy under the current situation. Having a fiscal problem that urgently needs to be addressed, the reductions in all public spending can result in the deduction of available resources for regional policy. This will result not only in smaller effectiveness of the interventions, but also Greek Regions will not be able to comply with the requirements and the goals of the Europe 2020 Strategy. Furthermore, not all the Greek Regions have the same economic structure. So, the changes that must be applied must have a diversified character for each region. Also, the provisions for the 2014-2020 Programming Period do not take into account the crisis in the Greek Economy and estimate Greek Regions as having moved from the "Cohesion" goal (with the exemption of 3 Regions) and this implies that the allocated funds will be lesser in the next years. With all that in mind the paper concludes with some proposals for the review of the Greek Regional policy for the remaining of the 2007-2013 period and also some suggestions for the 2014-2020 period, assuming that there cannot be significant changes in the European context of the overall Cohesion Policy.
Keywords: R58; O21; 330; Economic Crisis; Greece; Regional Policy; European Cohesion Policy